Exploring the potential of local food in promoting cultural heritage tourism product in Bandar Maharani, Muar, Johor / Puteri Yuliana Samsudin ... [et al.] - Samsudin, Puteri Yuliana; Jamil, Nur'qhairanie; Sallehudin, Noor Syarafina; Mohd. Arshard, Wan Nur Rukiah (Universiti Teknologi MARA, Sabah, 2023)
Cultural tourism is based on collecting products classified as 'culture' offered in a destination area. Tourism products are one of the main attractions for tourists to travel to a place that produces or introduces tourism products. This study focuses on the potential of local food as a cultural heritage tourism product in introducing the identity of Bandar Maharani, Muar Johor. This paper explores the perceptions of local residents and tourists on local food. The existence of local food can attract tourists to try and taste the differences and uniqueness of the local food. The research was conducted in Bandar Maharani, Muar District. This study utilized qualitative and quantitative methods: observation and questionnaire surveys. Probability sampling in the form of a random sample was employed. The data analysis utilised the SPSS software. The findings lead to recommendations for improvements in tourism development in Bandar Maharani, such as promoting local food through social media and upgrading tourism facilities around Bandar Maharani. This study can also help the local authority plan and boost the tourism sector in Bandar Maharani, Muar, Johor.